2016
DOI: 10.1080/00365521.2016.1267793
|View full text |Cite
|
Sign up to set email alerts
|

Mallory Weiss syndrome is not associated with hiatal hernia: a matched case–control study

Abstract: Dynamic changes inducing mucosal tension are more relevant determinants to develop MWS than gastro-esophageal junction location alone.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
3
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 5 publications
1
3
0
Order By: Relevance
“…Moreover, neither endoscopic findings of atrophic gastritis nor hiatal hernia were found in the 20 MWT patients. This was in accordance with a case-control study showing that hiatal hernia was not associated with MWT[22].…”
Section: Discussionsupporting
confidence: 93%
“…Moreover, neither endoscopic findings of atrophic gastritis nor hiatal hernia were found in the 20 MWT patients. This was in accordance with a case-control study showing that hiatal hernia was not associated with MWT[22].…”
Section: Discussionsupporting
confidence: 93%
“…Hiatus hernia is discussed as a potential risk factor for MWS for decades and hiatus hernia is a common factor in reflux esophagitis 26–28 . Nevertheless, a more recent case-control study found no correlation between hiatal hernia and MWS 29 . In our study, there were 11,655 cases of diaphragmatic hernia (19.7% of all cases; 31.8% in the group with reflux esophagitis).…”
Section: Discussioncontrasting
confidence: 53%
“…Most cases of MWS are mild and may even go unnoticed. Large studies on MWS are scarce, with only 8 studies with over 100 cases in our literature review since 2000 [4, 12‒18]. A population-based study found 2,342 cases of MWS in 783,037 EGDs (0.3%), of which 421 (18%) has active bleeding [13].…”
Section: Discussion/conclusionmentioning
confidence: 99%
“…Large studies on MWS are scarce, with only 8 studies with over 100 cases in our literature review since 2000 [4, 12‒18]. A population-based study found 2,342 cases of MWS in 783,037 EGDs (0.3%), of which 421 (18%) has active bleeding [13]. Another study reported that 71 of 546 iatrogenic MWS (13%) required endoscopic hemostatic procedures [14].…”
Section: Discussion/conclusionmentioning
confidence: 99%